CD4 is a critical component of the receptor for human herpesvirus 7: interference with human immunodeficiency virus. - Lusso, P (1994)
In this study, we demonstrate that the glycoprotein CD4, a member of the immunoglobulin superfamily, is a critical component of the receptor for human herpesvirus 7 (HHV-7), a recently discovered T-lymphotropic human herpesvirus. A selective and progressive downregulation of the surface membrane expression of CD4 was observed in human CD4+ T cells in the course of HHV-7 infection. Various murine monoclonal antibodies to CD4 and the recombinant soluble form of human CD4 caused a dose-dependent inhibition of HHV-7 infection in primary CD4+ T lymphocytes. Moreover, radiolabeled HHV-7 specifically bound to cervical carcinoma cells (HeLa) expressing human CD4. A marked carcinoma cells (HeLa) expressing human CD4. A marked reciprocal interference was observed between HHV-7 and human immunodeficiency virus (HIV), the retrovirus that causes the acquired immunodeficiency syndrome and also uses CD4 as a receptor. Previous exposure of CD4+ T cells to HHV-7 dramatically interfered with infection by both primary and in vitro-passaged HIV-1 isolates. Reciprocally, persistent infection with HIV-1 or treatment with the soluble form of gp120, the CD4-binding envelope glycoprotein of HIV-1, rendered CD4+ T cells resistant to HHV-7 infection. These data indicate that CD4 is critically involved in the receptor mechanism for HHV-7. The antagonistic effect between HHV-7 and HIV could be exploited to devise therapeutic approaches to AIDS.